PERNIKAHAN BEDA AGAMA DI INDONESIA DITINJAU DARI HUKUM ISLAM DAN HAK ASASI MANUSIA (HAM) - Karuniawan, Fathony; Adnan, Idul; Nuriskandar, Lalu Hendri (STIS Darussalam Bermi, 2022)
According to Islamic law, interfaith marriages are not permitted because they involve differences in faith. Based on the MUI fatwa Number: 4/MUNAS VII/MU/8/2005 which was issued as a result of the Second National Deliberation on 26 May to 1 June 1980 which determined that marriage between different religions is haram, the reasons are: a. Al-Qur'an Surah Al-Baqarah verse 221 explains that it is forbidden for Muslim men to marry non-Muslim women until they become believers. Apart from that, it also explains that it is forbidden for guardians to marry women under their responsibility to non-Muslim men. b. Al-Quran Surah Al-Mumtahanah verse 10 explains that believing men should not maintain their marriages with non-Muslim women, as well as non-Muslim women should be returned to Muslim men, because their marriages are forbidden by Allah. c. Al-Qur'an Surah Al-Tahrim verse 6 commands believers to guard and protect themselves and their families from the fire of hell. d. The words of the Prophet Muhammad SAW narrated by Imam Al-Tabarani taught that marriage is half of the teachings of religion. And we are instructed to be careful of the rest. e. The words of the Prophet Muhammad SAW narrated by Ibn. Al-Sura'i who taught about the importance of teaching religious education for parents to their children. Law Number 39 of 1999 concerning Human Rights in Indonesia, there is an explanation about freedom of religion, there is also freedom to marry and continue offspring, as stated in Article 10 paragraph (1 ) which states that every person has the right to form a family and continue their offspring through legal marriage. Thus, the right to carry out a marriage is limited by the Marriage Law. Meanwhile, in Article 2 of the Marriage Law, a valid marriage is a marriage carried out based on their respective religions and beliefs. This article is often seen as a prohibition against interfaith marriages, because marriages must be carried out according to their respective religions and beliefs, whereas it is impossible for one marriage to be carried out with two religious ceremonies. Therefore, in carrying out an interfaith marriage, one party should follow the religion of the other party. Religious freedom in Indonesia cannot be fully implemented, because there has been coercion by the institution of marriage on someone to embrace a certain religion in order to carry out a marriage. Keywords: Interfaith marriage, Islamic law, human rights